FAKTOR PREDISPOSING PERSALINAN SECTIO CAESAREA DI RSUD SIMO BOYOLAL - Yanti, Yanti; Dewi, Fitri Kusuma (Jurnal Kebidanan, 2024)
Background: Caesarean Section (CS) delivery should be understood as an alternative delivery when normal delivery is no longer possible. Although risky, the incidence of CS continues to increase in many countries including Indonesia. An initial survey at Simo Boyolali Hospital showed that CS deliveries have increased over time. Data from Medical Records in the last 2 years showed that in 2022, 718 mothers gave birth with 356 normal deliveries and 362 CS (50.4%). In 2023, there were 734 deliveries, of which 282 normal deliveries and 452 CS deliveries (61.5%). Purpose of the study: to determine the relationship between predisposing factors (age, gravida, frequency of ANC) and caesarean section deliveries at Simo Boyolali Hospital. Research method: Type of quantitative research, analytical survey, with a retrospective design. The research sample was 260 from a total population of 734 mothers giving birth at Simo Boyolali Hospital from January to December 2023, taken using Proportional simple random sampling. Data analysis using the chi square statistical test. Results of the study: Maternal age in this study was mostly in the non-risk age category, namely 197 respondents (75.8%) with gravida multipara, namely 176 respondents (67.7%) and with a majority of ANC frequency ? 6 times, namely 245 respondents (94.2%). The results of the statistical test for the maternal age factor and the gravida factor obtained a p value of 0.000 and for the ANC frequency factor, the p value was 0.001. Conclusions and Suggestions: There is a very significant relationship between the maternal age factor, gravida and ANC frequency with CS delivery at Simo Boyolali Hospital. For health workers to be more careful in screening pregnancy risk factors from age and gravida and to carry out education on the importance of regular ANC to support normal pregnancy and delivery. Keywords: Maternal Age, Gravida, ANC Frequency, Caesarean Delivery